Pengaruh Work-Life Balance, Disiplin Kerja, Lingkungan Kerja dan Kompensasi terhadap Kinerja Karyawan PT Slamet Langgeng Purbalingga - Iqbal Fadholi; Hermin Endratno; Akhmad Darmawan; Irawan Randikaparsa (Jurnal Ekonomi dan Pembangunan Indonesia, 2026)
This study aims to analyze the influence of Work-Life Balance, work discipline, work environment, and compensation on employee performance at PT. Slamet Langgeng Purbalingga. This study employed a quantitative approach using a survey method involving 100 respondents selected through questionnaire distribution to employees who met the research criteria. The collected data were analyzed using multiple linear regression with the assistance of SPSS statistical software. Hypothesis testing was conducted using the simultaneous F-test and the t-test to examine the effect of each independent variable on employee performance at a significance level of 5% (α = 0.05). The results indicate that Work-Life Balance, work discipline, work environment, and compensation simultaneously have a significant effect on employee performance. Partially, work discipline has the most dominant influence among the independent variables, while compensation shows a relatively lower effect compared to the other variables. These findings contribute theoretically to the development of human resource management literature, particularly regarding the factors influencing employee performance, and provide practical implications for companies in formulating policies to improve productivity, work effectiveness, human resource quality, and sustainable employee performance.